Is prepubertal growth adversely affected by sport? - Damsgaard, R.; Bencke, J.; Matthiesen, G.; Petersen, J. H.; Müller, J. (Medicine & Science in Sports & Exercise, 2000)
Purpose: To study the effect of genetic factors, birth weight, early childhood growth, sport, hours of training, and pubertal status on the stature and body mass index (BMI) of children aged 9-13 participating in sports at a competitive level. Methods: A total of 184 children (96 girls, 88 boys), competing in swimming, tennis, team handball, and gymnastics, were investigated, assessing their height, weight, pubertal development, and BMI. Of these, 137 (76 girls, 61 boys) returned a questionnaire, which enabled us to determine height and BMI at age 2-4, birth weight, and parental heights. Results: Significant differences in standard deviation scores (SDS) for actual height and for height at age 2-4 were found in both sexes between the four sports. In girls, BMI SDS was significantly different between the four sports, whereas no difference was found in boys. Each sport investigated separately showed no change in height SDS and BMI SDS between ages 2-4 and 9-13. A regression analysis showed that target height, height at age 2-4, and pubertal status had a significant impact on actual height. Interestingly, the type of sport and hours of training per week had no effect on height SDS. In boys, BMI at age 2-4 and pubertal status had a significant effect on actual BMI, whereas in girls, only BMI at age 2-4 was significant. Conclusions: The results suggest that prepubertal growth is not adversely affected by sport at a competitive level and that constitutional factors are of importance for choice of sport in children. Med. Sci. Sports Exerc., Vol. 32, No. 10, pp. 1698-1703, 2000